A comparative analysis of family roles and values - Papoyan, Varduhi; Galstyan, Alina; Harutyunyan, Narine (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
This study aims to identify the values in family relationships within the context of traditional and egalitarian family structures. It examines the differences between urban and rural families, focusing on role distribution, child-rearing practices, and the maintenance of family relationships․ Special attention is given to terminal and instrumental values, which shape family interactions, contribute to harmony, and influence parenting strategies. Empirical research highlights key differences in the value orientations of traditional and modern families, reflecting their adaptation to the changing social conditions. The findings reveal that traditional families emphasize preserving personal life, ensuring family well-being, and strengthening emotional bonds across generations. At the same time, egalitarian families focus on the equal distribution of responsibilities, professional self-realization, and social engagement. In contrast, rural families place greater importance on traditions, familial warmth, and values that promote family stability and strengthen intergenerational bonds. The family remains a fundamental element of the social structure, shaping individual identity, preserving cultural heritage, and contributing to societal stability. The article underscores the importance of studying family values and roles in the context of modern globalization and social transformation